Implementation of Hybrid Learning Models in Islamic Universities in Asian Countries - Muhammad Lukman Haris Firmansah; Allan Firman Jaya; Nurul Agustin; Maslakhah Witri Kusuma Dewi (Journal Emerging Technologies in Education, 2023)
Background. At this time technology has experienced increasingly advanced developments over time. Technology plays an important role in helping the learning process, the atmosphere in learning will be helped by the existence of learning methods such as the implementation of the hybrid model. Purpose. This study aims to determine the implementation of the hybrid learning model in Islamic universities in Asian countries.In this study, researchers conducted research using quantitative methods. Method. The results of this study indicate that this hybrid learning can be used as a learning model that is very suitable in tertiary institutions because it can create a conducive and effective learning atmosphere. Results. . From this research it can be concluded that the hybrid learning model can help students learn through content and instructions that are obtained online independently. Conclusion. The limitation in this study is that the researcher only conducted research at one of the universities located in Tanah Datar district, for this reason the researcher hopes that the next researcher will be able to conduct the same research, but in a different place so that he can continue this research.in Asian Country